Inflation expectations, learning, and supermarket prices: Evidence from survey experiments - Cavallo, Alberto (2017)
Information frictions play a central role in the formation of household inflation expectations, but there is no consensus about their origins. We address this question with novel evidence from survey experiments. We document two main findings. First, individuals in low inflation contexts have significantly weaker priors about the inflation rate. This finding suggests that rational inattention may be an important source of information frictions. Second, cognitive limitations also appear to be a source of information frictions: Even when information about inflation statistics is available, individuals still place a significant weight on inaccurate sources of information, such as their memories of the price changes of the supermarket products they purchase. We discuss the implications of these findings for macroeconomic models and policymaking.